Study on the Annual Variation Characteristics of Runoff in Yunnan - GU Guihua; LI Xuehui; YU Shoulong; DUAN Lusong (Renmin Zhujiang)
To study the annual variation characteristics of runoff in Yunnan Province and analyze the main influencing factors,based on the observed monthly and annual rainfall and runoff data of 9 representative hydrological stations in 6 major river basins in Yunnan from 1956 to 2016,this paper analyzes the annual runoff distribution in terms of the uniformity,concentration and relative variation range.The research shows that:①The uniformity coefficient (Cu) of runoff distribution in many years ranges from 0.55 to 1.21,and the concentration (Cn) ranges from 0.23 to 0.66,so the runoff is unevenly distributed in the whole province.②The Cu and Cn decrease in general.Especially after 2000,the annual distribution of runoff shows a trend of uniformity.③The runoff concentration is relatively high in the Yangtze River Basin and the Honghe River Basin,and the annual runoff distribution is flat in the Lancang River Basin and the Zhujiang River Basin.④The uniformity trend of annual runoff distribution is closely related to human activities in the basin.